1994
DOI: 10.1002/dc.2840110413
|View full text |Cite
|
Sign up to set email alerts
|

Oncocytic carcinoma of parotid gland: Fine‐needle aspiration and histologic findings

Abstract: A parotid gland mass in an elderly man was diagnosed as an oncocytic neoplasm with cellular pleomorphism and cytologic atypia by fine-needle aspiration. The histologic features showed a primary parotid malignant oncocytoma with metastasis in regional lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…6,[10][11][12][13] However, the oncocytic nature was confirmed in only three cases. 6,12,13 Electron microscopy and/or PTAH staining was used to show the presence of numerous cytoplasmic mitochondria in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,[10][11][12][13] However, the oncocytic nature was confirmed in only three cases. 6,12,13 Electron microscopy and/or PTAH staining was used to show the presence of numerous cytoplasmic mitochondria in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,[10][11][12][13] However, the oncocytic nature was confirmed in only three cases. 6,12,13 Electron microscopy and/or PTAH staining was used to show the presence of numerous cytoplasmic mitochondria in earlier studies. 6,12,13 In the present report, we readily showed immunoreactivity of the tumor cytoplasm by immunocytochemistry using monoclonal antimitochondrial antibody.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Acceptable criteria for the diagnosis of malignancy are local infiltration, perineural or intravascular invasion and the presence of regional or distant metastases. 14 The diagnosis of oncocytic carcinoma on aspirated material has been reported. 2,14,20 A review of several large series on FNAC of salivary gland lesions revealed little about diagnostic accuracy in oncocytomas.…”
Section: Verma and Kapilamentioning
confidence: 99%